An Unexpected Cause of a Subcutaneous Nodule: A Case Report of Dirofilaria Infection - Bruno Man-Hon Cheung; Yi-Lan Huang; Yie-Wen Lin; Yung-Sen Chang; Shian-Min Liu (Case Reports in Infectious Diseases)
Humans are not natural hosts of Dirofilaria; however, pulmonary or subcutaneous infections may occur through mosquitoes transmission. Patients presenting with simple subcutaneous nodules may not seek early medical attention, and hence systemic involvement through hematogenous spread may occur. Definitive diagnosis of Dirofilaria infection is made by histopathological examinations of the infected tissues. We report a patient with an incidental diagnosis of Dirofilaria infection confirmed by histopathological findings of a subcutaneous nodule on the right thigh. The source of infection remains unknown.